Humanizing Sustainability : Analisis Pengungkapan Aspek Sosial ESG LQ45 Tahun 2024 - Anas, Nurul Inayah Aulia; Nurhidayana, Nurhidayana; Abidin, Nur Hikma Lestari; Resmail, Aliyah Aqila (Jaanur Elbarik Indonesia, 2025)
This research aims to explore how companies included in the LQ45 index disclose social aspects within the Environmental, Social, and Governance (ESG) framework in their 2024 sustainability reports. Through document analysis of Sustainability Reports and supporting literature, this study maps the quality and comprehensiveness of disclosures based on GRI 401–406 social indicators. The results show disparities between sectors: companies in the mining, energy, and banking sectors have more detailed disclosures, particularly on employment and occupational safety aspects, while the FMCG, property, and technology sectors still show limited disclosures, particularly on issues of diversity, industrial relations, and anti-discrimination